2005
DOI: 10.1093/ndt/gfi133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NH4Cl intake on renal growth in rats: role of MAPK signalling pathway

Abstract: The present study confirms that NH4Cl-induced acidosis causes disturbances in renal sodium handling. In addition, these findings demonstrate a sustained pre-stimuli activation of kidney MAPK/ERKs signalling pathways in the NH4Cl-treated rats that may correlate with an increased rate of kidney hypertrophy and a transient renal tubule inability to handle sodium. Thus, the altered renal electrolyte handling may result from a reciprocal relationship between the level of renal tubule metabolic activity and ion tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In this regard, we have previously shown that chronic metabolic acidosis, caused by NH 4 Cl feeding, leads to nephron hypertrophy and to a decreased watersalt reabsorption by the kidneys [1,25,26]. Since renal ion tubule transport is highly dependent on mitochondrial energy and because mitochondria have been implicated in a variety of metabolic disorders, we examined mitochondrial energy-linked functions in chronic metabolic acidotic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, we have previously shown that chronic metabolic acidosis, caused by NH 4 Cl feeding, leads to nephron hypertrophy and to a decreased watersalt reabsorption by the kidneys [1,25,26]. Since renal ion tubule transport is highly dependent on mitochondrial energy and because mitochondria have been implicated in a variety of metabolic disorders, we examined mitochondrial energy-linked functions in chronic metabolic acidotic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in rats [1,2] metabolic acidosis induced by NH 4 Cl resulted in an absolute increase in kidney mass associated with disturbances in renal sodium handling that were preceded by activation of kidney MAPK/ERKs signalling pathways. Under these acidotic conditions, the altered renal electrolyte handling may have resulted from a lack of energy availability for ion transport due to the high energy demand for renal anabolic processes [1].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, ERK activation in this proximal tubule like cell is associated with NHE3 inhibition, not unlike NHE3 inhibition and reduced bicarbonate absorption by ERK activation in the thick ascending limb of the nephron [23]. This effect plus ERK activation dependent depolarization of mitochondria may contribute to the profound natriuresis observed in vivo with metabolic acidosis [5,[24][25][26]. Metabolic base generation requires that glutamate be oxidized by glutamate dehydrogenase within the mitochondrial matrix and coupled to Complex I via NADH+H + .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Signal-Regulated Kinase (ERK) activation occurs in kidney cells in response to metabolic acidosis in vivo as well as in cultured kidney cells [5][6][7] suggesting ERK activation plays a role in physiological responses. However, the underlying mechanisms relating TRO-induced ERK activation and cellular acidosis requires further clarification.…”
Section: Introductionmentioning
confidence: 99%